2013
DOI: 10.1136/oemed-2012-101087
|View full text |Cite
|
Sign up to set email alerts
|

Are regulations effective in reducing construction injuries? An analysis of the Italian context

Abstract: Objectives At the end of the 1990s, as required by European Directive 92/57/EEC, two laws were enacted in Italy which laid down safety and health requirements for construction sites: Decree 494/96 and Decree 528/99. The aim is to evaluate the impact on injury rates due to actions performed by a group of eight regions that planned formalised programmes to enforce the laws around the year 2000. Methods Using the Work History Italian Panel-Salute integrated database, which extends from 1994 to 2005, total and ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Other studies [27,39] have confirmed that compliance with certain new legal provisions significantly reduces the number of work accidents. In particular, in 2006, a new regulation on subcontracting in the construction sector was introduced in Spain.…”
Section: General Development Of the Accidents Rate In The Constructiomentioning
confidence: 87%
See 2 more Smart Citations
“…Other studies [27,39] have confirmed that compliance with certain new legal provisions significantly reduces the number of work accidents. In particular, in 2006, a new regulation on subcontracting in the construction sector was introduced in Spain.…”
Section: General Development Of the Accidents Rate In The Constructiomentioning
confidence: 87%
“…[36] Although previous studies showed evidence of the effectiveness of other interventions, [27,36,37,38,39,40] this is the first available analysis of the effectiveness of renewing the scaffolds in construction enterprises in order to incorporate standardized ones.…”
Section: General Development Of the Accidents Rate In The Constructiomentioning
confidence: 99%
See 1 more Smart Citation
“…In Italy, research focused on effectiveness evaluation of work inspection is scarce [Farina et al, ]. In 2009, the Ministry of Health financed a study to evaluate the impact of targeted inspections for injury prevention in manufacturing industries.…”
Section: Introductionmentioning
confidence: 99%
“…Farina and colleagues investigated the impact of national legislation on minimum safety and health requirements in 1999 on injuries at construction sites (56). Total and serious injury rates in the construction sector were calculated from 1994-2005, based on an integrated database (ie, Work History Italian Panel Salute).…”
Section: Interrupted Time Series Designmentioning
confidence: 99%